2022
DOI: 10.3389/fimmu.2022.903771
|View full text |Cite
|
Sign up to set email alerts
|

Immune Effects of Macrophages in Rheumatoid Arthritis: A Bibliometric Analysis From 2000 to 2021

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease characterized by macrophage activation. The current characteristics, hotspots, and research frontiers of macrophage-related RA were analyzed using bibliometric analysis. Relatedpapers published from 2000 to 2021 in the Web of Science database were retrieved. The diagrams were generated and analyzed using the bibliometric software package. VOSviewer and CiteSpace were used to evaluate and visualize the research trends and hotspots in macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Co-cited authors are two or more authors cited simultaneously in one or more papers ( Xu et al, 2022 ). Figure 4A illustrates the network mapping of co-cited authors.…”
Section: Resultsmentioning
confidence: 99%
“…Co-cited authors are two or more authors cited simultaneously in one or more papers ( Xu et al, 2022 ). Figure 4A illustrates the network mapping of co-cited authors.…”
Section: Resultsmentioning
confidence: 99%
“…This bibliometrics analysis was performed by referring to the previous relevant literature. , The Web of Science Core Collection (WoSCC) database from Clarivate Analytics encompasses over 15,000 peer-reviewed journals from more than 250 disciplines worldwide . WoSCC is recognized as one of the most comprehensive and authoritative databases for accessing global academic information, making it the optimal database for bibliometric analysis .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…[73,74] Regulatory T cells (Tregs) and M2 macrophages are also considered to play an important role in anti-inflammation, which can secrete various anti-inflammatory factors, such as IL-10 and transforming growth factor-𝛽 (TGF-𝛽), to protect the body from damage caused by excessive inflammatory responses. [75,76] On the other hand, they can be used to boost the immune response when immunity is deficient and insufficient to fight against pathogens. For example, several clinical studies (NCT04896606, NCT04365101) have shown that cytotoxic T cell lymphocytes (CTLs) and NK cells are promising to compensate for the exhausted immune system in COVID-19 patients who suffer from lymphopenia.…”
Section: Living Cellsmentioning
confidence: 99%